Advances in drug design based on the amino acid approach: Taurine analogues for the treatment of CNS diseases - Chung, Man Chin [UNESP]; Malatesta, Pedro [UNESP]; Bosquesi, Priscila Longhin [UNESP]; Yamasaki, Paulo Renato [UNESP]; dos Santos, Jean Leandro [UNESP]; Vizioli, Ednir Oliveira [UNESP] (MDPI, 2012)
Amino acids are well known to be an important class of compounds for the maintenance of body homeostasis and their deficit, even for the polar neuroactive aminoacids, can be controlled by supplementation. However, for the amino acid taurine (2-aminoethanesulfonic acid) this is not true. Due its special physicochemical properties, taurine is unable to cross the blood-brain barrier. In addition of injured taurine transport systems under pathological conditions, CNS supplementation of taurine is almost null. Taurine is a potent antioxidant and anti-inflammatory semi-essential amino acid extensively involved in neurological activities, acting as neurotrophic factor, binding to GABA A/glycine receptors and blocking the excitotoxicity glutamate-induced pathway leading to be a neuroprotective effect and neuromodulation. Taurine deficits have been implicated in several CNS diseases, such as Alzheimer's, Parkinson's, epilepsy and in the damage of retinal neurons. This review describes the CNS physiological functions of taurine and the development of new derivatives based on its structure useful in CNS disease treatment.&; 2012 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Amino acid; Analogs; CNS; Taurine; 2 aminoethylmethylsulfone; 2 aminoethylphosphonic acid; 2 phthalimidoethanesulfonamide derivative; 4 aminobutyric acid A receptor; acamprosate; alcohol; aminocyclohexaenesulfonic acid; aniline 2 sulfinic acid; anticonvulsive agent; cysteic acid; dimethyltaurine; ethanolamine sulfate; glutaurine; glycine receptor; homotaurine; n methyl thiomorpholine 1,1 dioxide; n pivaloyltaurine; piperidine 3 sulfinic acid; tau 15; taurepar; taurine; taurine derivative; taurocholic acid; taurolidine; tauropyrone; thiomorpholine 1,1 dioxide; trimethyltaurine; unclassified drug; valproyltaurinamide derivative; alcoholism; Alzheimer disease; amino acid substitution; anticonvulsant activity; bipolar disorder; blood brain barrier; brain edema; brain ischemia; central nervous system disease; central nervous system tumor; CLogP; digestive system cancer; dose response; drug design; drug efficacy; drug potency; drug receptor binding; drug structure; drug synthesis; excitotoxicity; human; hyperthermia; hypothermia; lipophilicity; low drug dose; neuromodulation; neuroprotection; nonhuman; Parkinson disease; retina disease; review; seizure; spinal cord compression; statistical parameters; structure activity relation; toxicity testing